Analisis Pengaruh Keputusan Investasi, Pendanaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Pada Perbankan Syariah Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) - Hariyanto, Hariyanto, Dr. Rini Kuswati, S.E., M.Si (2016)
The purpose of this study to determine the effect on the value of investment decisions on Islamic banking firm listed on the Stock Exchange in 2011-2013. To determine the influence funding decisions on firm value on Islamic banking listed in the Stock Exchange in 2011-2013. To determine the effect of dividend policy on firm value on Islamic banking listed in the Stock Exchange in 2011-2013. The population of this research is all companies listed on the Indonesia Stock Exchange. The sampling technique in this study using purposive sampling sampling based on certain criteria. Based on the results of KI variables have a significant influence on the NP. KP variables have a significant influence on NP.Variabel KD did not have a significant effect on the NP. Results of F> F table (16.919> 3.15), then Ho is rejected, Means jointly variable KI, KP and KD jointly affect the NP. The result of the calculation to the value of R2 obtained in multiple regression analysis obtained with a coefficient of determination adjusted-R2 of 0.675. This means that 67.5% variation of the variable value of the company can be explained by the variable KI, KP and KD while the remaining 32.5% is explained by other factors outside the model studied.